Pelatihan Fotografi Produk bagi Pelaku UMKM di Kelurahan Baros, Kecamatan Cimahi Tengah - Wijaksono, Dimas Satrio; Nuraeni, Reni; Yusanto, Freddy; Melano, Fiqie Lavani; Pramitha, Jalesita Putri (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Product photography training for MSMEs in Baros Village, Central Cimahi, aims to improve the visual and digital skills of business owners in marketing their products. This activity was carried out through three main stages: pre-production, production, and post-production. In the pre-production stage, material preparation, consultation with MSME players, and provision of tools were carried out. The production stage includes theory delivery, hands-on practice, and evaluation of photography skills. Meanwhile, the post-production stage focused on documentation, publication of results, and assessment to ensure the sustainability impact of the training. The results of the training showed a significant improvement in participants' ability to take quality product photos, which supported product branding and promotion through digital platforms. The program also helped reduce MSMEs' dependence on external services, thus optimizing their operational budget. With improved digital literacy, MSME players are able to reach a wider market, strengthen competitiveness, and support local economic inclusion.